Korelasi Perlakuan Lapang terhadap Galat Tereduksi Poligon Terbuka - Didik Kuswadi; Kelik Istanto; Iskandar Zulkarnain (Jurnal Ilmiah Teknik Pertanian - TekTan, 2011)
The surveyor often apply unreferenced opened traverse method in basic framework surveying defined, especially, surveying which emphasized in long trace surveying. The objectives of this research are (1) Define procedure in unreferenced opened traverse in order that it may be corrected and (2) Predict similar nomenclature coordinates deviation value of unreferenced opened traverse and unreferenced one with treatments. Geometric approach as treatment was given in four points of unreferenced opened traverse by reading ruler marks, horizontal, and vertical angels which referenced to prior point and prior one with defined interval. The both computation result show that the treatment done able to reduce similar nomenclature coordinates deviation of unreferenced opened traverse to closure traverse. Systematic errors reduced was defined as reducing area which made by unreferenced opened traverse coordinates and it one with treatment to closure traverse. The reduce value was 42,888 m2 to 28, 326 m2 or in percent the systematic errors reduced was 33,95 %.Â Keywords: field treatment, traverse, systematic errors reduced